Exploring the effects of speed and scale on a ship’s form factor using CFD - Terziev, Momchil; Tezdogan, Tahsin; Demirel, Yigit Kemal; Villa, Diego; Mizzi, Simon; Incecik, Atilla (International journal of naval architecture and ocean engineering, 2021)
The problem of predicting a ship’s form factor and associated scale effects has been subject to many investigations in recent years. In this study, an attempt is made to investigate whether the form factor is influenced by a change in the ship’s speed by numerically modelling a geosim series of the KCS hull form by means of a RANS solver. The turbulence dependence of the problem is also studied by altering the closure model among three widely used approaches (the k-ω, k-ω SST, and k-ε models). The results show that at very low speeds (Froude numbers in the range of 0.02–0.06) the numerical model predicts changes in the form factor of a ship between 10% and 20%, depending on the turbulence model and scale factor choices. As the speed is increased further, the form factor exhibits little change, usually in the range of 1% or less. Simulations where the Reynolds number is changed by approximately two orders of magnitude, achieved by altering the value of viscosity, confirmed that the form factor can be considered Froude-dependent only for low speeds, predicting essentially identical values when high speed cases are considered. •The scale effect on a ship’s form factor is investigated numerically.•Effects of scale factor and speed are considered using linear and viscous scaling.•Turbulence dependence is found to be of greater importance than any other parameter.•Results reveal a Froude number dependence at low speeds.